How is the elementary students' creative thinking process in solving fraction problems using geometric and algebraic solutions? - Triyani, Septi; Budayasa, I Ketut; Amin, Siti Maghfirotun (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
This study aimed to explore students’ creative thinking process in fifth- grade elementary school in fraction problem solving based on gender differences. Subjects consisted of one male and one female with high mathematical ability. Data were collected by task-based interviews and analyzed through the sequence: data classification, data reduction, data presentation, interpretation, and conclusions. The creative thinking process in this research is a series of stages that students go through in creative thinking, including: exploring facts, identifying problems, generating ideas and completing ideas to produce solutions. By these stages, the subjects produced solutions in geometric and algebraic that showed their creative thinking that fulfilled fluency, flexibility and novelty. The subjects used algorithm solutions by repeating the completion steps. In this research, both subjects related their algebraic solutions with geometric solutions that has been produced. It was found that geometric solutions supported the subjects to deliver algebraic solutions and they related their understanding of fractions concepts to solve the problem. The more students’ knowledge or experiences associated with the problem, the more ideas for solutions they found. In this research, it was also found that there were some similarities and differences between the creative thinking processes of both subjects.